To rearrange the equation \( A = \frac{1}{2}(b_1 + b_2)h \) for \( b_1 \), follow these steps:
-
Start with the original equation: \[ A = \frac{1}{2}(b_1 + b_2)h \]
-
Multiply both sides by \( 2 \): \[ 2A = (b_1 + b_2)h \]
-
Divide both sides by \( h \): \[ \frac{2A}{h} = b_1 + b_2 \]
-
Subtract \( b_2 \) from both sides to isolate \( b_1 \): \[ b_1 = \frac{2A}{h} - b_2 \]
Now let's compare this final expression to the options provided:
- \( b1 = \frac{2A - b2}{h} \) - Incorrect
- \( B1 = \frac{h}{2A} - B2 \) - Incorrect
- \( B1 = \frac{2A}{h} - B2 \) - Correct
- \( BY = \frac{h - B2}{2A} \) - Incorrect
The correct rearranged equation for \( b_1 \) is: \[ b1 = \frac{2A}{h} - b2 \]
Thus, the third option \( B1 = \frac{2A}{h} - B2 \) is the correct answer.